MINI REVIEW SENYAWA POLIFENOL PADA KOPI : PENGARUH PENGOLAHAN, METABOLISME DAN HUBUNGANNYA DENGAN KESEHATAN - Yusmarini ' (Jurnal Sagu, 2011)
Coffe is one of the main resources of polifenol compound, especially chlorogenat acidwhich is known have the capacity as antioxidant. There are the changes of chlorogenat acidduring processing, preparation and digestion by in vitro and in vivo which is have an impact toits availability and power. Coffe consumption reported can decrease blood rate on mice butincrease the total of plasma homocystein on humans. The high homocystein concentration inblood is one of the risk factor for degenerative diseases. Advanced researchs need to support thestatements.